2018
DOI: 10.1186/s12917-018-1331-5
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale study of a poultry trading network in Bangladesh: implications for control and surveillance of avian influenza viruses

Abstract: BackgroundSince its first report in 2007, avian influenza (AI) has been endemic in Bangladesh. While live poultry marketing is widespread throughout the country and known to influence AI dissemination and persistence, trading patterns have not been described. The aim of this study is to assess poultry trading practices and features of the poultry trading networks which could promote AI spread, and their potential implications for disease control and surveillance.Data on poultry trading practices was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…Moreover, because wholesalers might sell birds to retailers in the same LBM (23), virus amplification might be increased through the presence of wholesalers. The higher prevalence of A(H9) virus in broilers than in Sonali and Desi might result from differences in the structure of their respective value chains (23). Depending on the chicken type, different value chain actors might be involved and their trading practices might differ (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, because wholesalers might sell birds to retailers in the same LBM (23), virus amplification might be increased through the presence of wholesalers. The higher prevalence of A(H9) virus in broilers than in Sonali and Desi might result from differences in the structure of their respective value chains (23). Depending on the chicken type, different value chain actors might be involved and their trading practices might differ (23).…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of A(H9) virus in broilers than in Sonali and Desi might result from differences in the structure of their respective value chains (23). Depending on the chicken type, different value chain actors might be involved and their trading practices might differ (23). The amount of time chickens spend with traders, the density at which chickens are kept in flocks of traders, and the frequency of contact with chickens from other flocks might vary with chicken type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two cross-sectional studies were conducted in Chittagong and Cox's Bazaar districts, which were identified as the main districts supplying chickens to Chittagong City Live Bird Markets (CCLBMs) (Moyen, 2019;Moyen et al, 2018). Backyard chicken farms were surveyed between February and April 2016, and commercial broiler and layer chicken farms between February and April 2017.…”
Section: Methodsmentioning
confidence: 99%